ANALISIS BIOEKONOMI DAN OPTIMASI PENGELOLAAN SUMBER DAYA IKAN LAYANG DI PERAIRAN KABUPATEN MUNA SULAWESI TENGGARA (Bioeconomic Analysis and Resource Management Optimization of Mackerel Scad in Muna District, South East Sulawesi) - Wa Ode Piliana; Tridoyo Kusumastanto; . Diniah (Bogor Agricultural University, 2015)
ABSTRACTThe resource utilization of mackerel scad (Decapterus spp.) has been increasing in Muna waters which will be able to reduce the fish stock and if it exceeds the carrying capacity, it will lead to